Interaction of starch branching enzyme 3 and granule-bound starch synthase 1 alleles increases amylose content and alters physico-chemical properties in japonica rice (Oryza sativa L.) - Shim, Kyu-Chan; Adeva, Cheryl; Kang, Ju-Won; Luong, Ngoc Ha; Lee, Hyun-Sook; Cho, Jun-Hyeon; Kim, HyunJung; Tai, Thomas H.; Ahn, Sang-Nag (Frontiers in Plant Science, 2022)
Four near-isogenic lines (NILs) with different allele combinations of the starch branching enzyme 3 (SBE3) and granule-bound starch synthase 1 (GBSS1) were developed by crossing the japonica rice cultivars “Dodamssal” and “Hwayeong.” The associations between sequence variations in SBE3 and GBSS1, and starch-related traits were investigated. These sequence variations led to changes in seed morphology, starch structure, starch crystallinity, amylopectin chain length distribution, digestibility, apparent amylose content (AAC), and resistant starch content (RS). SBE3 and GBSS1 showed genetic interaction in regulating AAC and RS. Gene expression profiling of panicle tissues revealed significant differences in expression levels of GBSS1, SBE3, and other starch-related genes among the four NILs, indicating that variations in GBSS1 and SBE3 changed the expression level of starch-related genes. These variations contributed to the changes observed in AAC, RS, and physico-chemical characteristics of the rice starch from the NILs.